Legal Protection Againts Workers/Labours Who Are Not Participants of Work Accident Guarantee Program : Perlindungan Hukum Terhadap Pekerja/Buruh Yang Bukan Peserta Jaminan Kecelakaan Kerja - Puspitasari, Dara; Kurniawan, Rizki; Noer, Zakiah; Mashudi; Nurhidayah, Maulida (Universitas Muhammadiyah Sidoarjo, 2022)
Work Accident Guarantee Program (JKK) is one form of welfare and legal protection for workers who experience work accidents. However, in fact, there are still many companies that do not register their workers in the Work Accident Guarantee Program (JKK) which was initiated by the Employment Guarantee Agency or commonly called BPJS Employment. Furthermore, the authors raise the formulation of the problem, namely: (1) What are legal sanctions against employers if they do not register their workers in the Work Accident Guarantee Program based on Chapter 4 of Government Regulation Number 44 of 2015. (2) How is the legal protection for workers/labourers who are not registered in the Work Accident Guarantee Program. The research is a type of legal research using normative legal research methods which is analyze through statute approach, conceptual approach, and historical approach. The result of this research shows that, Employers who do not register their workers in the Work Accident Guarantee Program (JKK) will receive administrative sanctions, either in the form of fines, written warnings, or not receiving certain public services. The rights of workers who experience work accidents both from the cost of transportation, care, and treatment, as well as wages for not being able to do work are the responsibility of the employer. In addition, since starting to work, the worker concerned can also register himself in the Work Accident Guarantee Program (JKK) and charge the employer with the collection of contributions.